Assassinations and Murder in Modern Italy
VIII, 246 p. 1 illus.
Keywords: An extraordinary series of murders and political assassinations has marked contemporary Italian history, from the killing of the king in 1900 to the assassination of former prime minister Aldo Moro in 1978. This book explores well-known and lesser-known assassinations and murders in their historical, political and cultural contexts.